Considering Caliphate and Democracy in Islam: A Comparison of The Ottoman Dynasty and The Indonesian State - Alfikri, Ahmad Faiz Shobir; SJ, Fadil (POLITEA, 2024)
The Ottoman Dynasty was one of the largest forms of Islamic government in history. This study aims to investigate and understand the comparison between the concept of the caliphate in the Ottoman Dynasty, one of the largest Islamic empires in history, and the form of a modern state with democracy, namely the State of Indonesia. This study uses comparative historical analysis, taken from primary sources, historical records, and scientific literature to trace the evolution of governance in the Ottoman Dynasty and the State of Indonesia. The results of this study indicate that there is no standard form of state practice in Islam. The monarchy system in the form of a caliphate state used by the Ottomans is in line with that conveyed by Ibn Abi Rabi who supports a monarchical form of government. The democratic system in the form of a republican state implemented in Indonesia is identical to the concept of Imamah conveyed by al-Mawardi. Any idea or formulation about state practice is permitted in Islam as long as it does not deviate from the references to the Qur'an and Hadith.